Dynamics of nuclear recoil: QM-BOMD simulations of model systems following β-decay. Issue 45 (10th November 2021) - Fromsejer, Rasmus; Mikkelsen, Kurt V.; Hemmingsen, Lars
Abstract : The effect of recoil from a β − nuclear decay on the dynamics of a protein model system is investigated using QM Born–Oppenheimer molecular dynamics. Abstract : The kinetic recoil energy received by the daughter nucleus in a nuclear decay is often large enough to affect the structure around the nucleus in chemical systems. The coinciding element change which typically occurs in a nuclear decay may additionally incur a structural reorganization. The effects of these phenomena on chemical systems where radio-isotopes are used are often little-known or neglected because the dynamics of nuclear decay is difficult to observe experimentally. In this work, QM-MD simulations are used to investigate local fs to ps dynamics following the β-decay of 111 Ag to 111 Cd in systems modelled on the metal-sensing CueR protein. An adiabatic approximation is applied, assuming that the electronic structure relaxes rapidly after the decay. PM7-MD simulations of recoil dynamics of the model systems show significant structural changes and bonding interactions that depend on the magnitude and direction of the recoil. We find that, in general, the kinetic recoil energy is rapidly distributed (<5 ps) uniformly throughout the systems in the studied scenarios.